Impact of Islamic on Sustainable Development Goals (SDGs) - Ainul Furqon; Yasid Yasid; Mukhid Mukhid (Penelitian dan Pengembangan Ilmu, 2024)
This research examines the contribution of zakat and waqf in supporting the Sustainable Development Goals (SDGs) in Muslim-majority countries. Islamic philanthropy, through zakat and waqf, has great potential to reduce poverty, improve health and education, and promote gender equality and environmental sustainability. The research method uses a systematic literature review approach by applying PRISMA guidelines to identify and analyze relevant articles. The research results show that zakat and waqf not only fulfill religious obligations but also play an important role in sustainable socio-economic development. The implications of this research emphasize the importance of improving transparency, governance and infrastructure to optimize the contribution of zakat and waqf to achieving the SDGs.